Associated factors for recommending HBV vaccination to children among Georgian health care workers - Butsashvili, Maia (BioMed Central, 2012)
BACKGROUND: Most cases of hepatitis B virus (HBV) infection and subsequent liver diseases can be prevented with universal newborn HBV vaccination. The attitudes of health care workers about HBV vaccination and their willingness to recommend vaccine have been shown to impact HBV vaccination coverage and the prevention of vertical transmission of HBV. The purpose of this study was to ascertain the factors associated with health care worker recommendations regarding newborn HBV vaccination. METHODS: A cross-sectional study of prevalence and awareness of hepatitis B and hepatitis B vaccine was conducted among randomly selected physicians and nurses employed in seven hospitals in Georgia in 2006 and 2007. Self-administered questionnaires included a module on recommendations for HBV, HCV and HIV. RESULTS: Of the 1328 participants included in this analysis, 36% reported recommending against hepatitis B vaccination for children, including 33% of paediatricians. Among the 70.6% who provided a reason for not recommending HBV vaccine, the most common concern was an adverse vaccine event. Unvaccinated physicians and nurses were more likely to recommend against HBV vaccine (40.4% vs 11.4%, PR 3.54; 95% CI: 2.38, 5.29). Additionally, health care worker age was inversely correlated with recommendations for HBV vaccine with older workers less likely to recommend it. CONCLUSION: Vaccinating health care workers against HBV may provide a dual benefit by boosting occupational safety as well as strengthening universal coverage programs for newborns.